Linear Programming Dengan Metode Primal Simpleks (Kasus Maksimasi) - Chandra, Deddy; Vesuvius, Deric; Octoria Hulu, Publius; Choumuangpuak, Ronaldo; Tanaka, Leony; Gultom, Pesta (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The culinary industry in Indonesia, particularly the dimsum sector, is undergoing rapid development in response to increasing consumer demand for practical and flavorful ready-to-eat meals. This study aims to analyze and optimize the production strategy of Dimsum Kota Medan by applying linear programming using the primal simplex method. The research adopts a case study approach, with data collected through direct interviews and observations to identify production goals, decision variables, and existing operational constraints such as labor, raw materials, and time availability. The simplex method is then applied to determine the optimal production combination that yields the highest profit. The findings show that to achieve a maximum daily profit (Zmax) of IDR 19,800,000, the enterprise should produce 60 portions of original dimsum (X1) and 60 portions of hakau dimsum (X2). Although the model operates under the assumption of linearity and does not capture all external market dynamics, it offers practical guidance for decision-making in resource allocation. This study demonstrates the relevance of mathematical optimization techniques in enhancing profitability for small and medium-sized culinary enterprises in a competitive market environment.